2006
DOI: 10.2527/jas.2005-736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-sugar ryegrass silage and mixtures with red clover silage on ruminant digestion. 2. Lipids1

Abstract: The experiment investigated the digestion of lipids from different forage silages in beef steers. Six Hereford x Friesian steers prepared with rumen and duodenal cannulas were given ad libitum access to a high-sugar grass silage, control grass silage, red clover silage, or mixtures of the red clover and each of the grass silages (50:50, DM basis). The experiment was conducted as an incomplete 5 x 5 Latin square, with an additional randomly repeated sequence. Total fatty acid and C18:3n-3 concentrations were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
30
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 42 publications
(59 reference statements)
13
30
2
Order By: Relevance
“…Lee et al (2003) found in an in vitro experiment that a high inclusion of WSC in the diet induced a shift towards fermentation of WSC rather than fibre digestion, which suggests a shift away from fibrolytic bacteria. In contrast, there was no effect on C18 biohydrogenation when feeding high-sugar grass silage compared with a control silage (Lee et al, 2006). The higher concentration of 18:3n-3 in milk from cows offered the RC-G silage compared with the grass silages is in accordance with earlier studies.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al (2003) found in an in vitro experiment that a high inclusion of WSC in the diet induced a shift towards fermentation of WSC rather than fibre digestion, which suggests a shift away from fibrolytic bacteria. In contrast, there was no effect on C18 biohydrogenation when feeding high-sugar grass silage compared with a control silage (Lee et al, 2006). The higher concentration of 18:3n-3 in milk from cows offered the RC-G silage compared with the grass silages is in accordance with earlier studies.…”
Section: Discussionsupporting
confidence: 90%
“…The concentrations of fatty acids in the 3 silages are lower than typical reported values for ryegrass, red clover, and cocksfoot, although the proportions of individual fatty acids are comparable with the literature (Lee et al, 2006a;Dierking, 2008;Halmemies-Beauchet-Filleau et al, 2013). This may relate to the greater maturity (second cut) of the crops in the current study as shown by their fiber composition, as maturity is related to lower fatty acid content of herbage (Dewhurst et al, 2001).…”
Section: Silage Compositionsupporting
confidence: 75%
“…This is consistent with net gain due to microbial fatty acid synthesis de novo in cattle fed diets containing low amounts of lipid, such as forage-only diets (Lee et al, 2006a;Halmemies-Beauchet-Filleau et al, 2013). The response was greater with CO as exemplified by a greater proportional increase in fatty acids associated with microbial lipids, namely C16:0 and BOC fatty acids (Vlaeminck et al, 2006).…”
Section: Fatty Acid Metabolism Across the Rumensupporting
confidence: 74%
See 2 more Smart Citations